MIR31HG, a potential lncRNA in human cancers and non-cancers - Ruan, Luxi; Lei, Jing; Yuan, Yihang; Li, Huizi; Yang, Hui; Wang, Jinyan; Zhang, Quanan (Frontiers in Genetics, 2023)
Long noncoding RNAs have recently attracted considerable attention due to their aberrant expression in human diseases. LncMIR31HG is a novel lncRNA that is abnormally expressed in multiple diseases and implicated in various stages of disease progression. A large proportion of recent studies have indicated that MIR31HG has biological functions by triggering various signalling pathways in the pathogenesis of human diseases, especially cancers. More importantly, the abnormal expression of MIR31HG makes it a potential biomarker in diagnosis and prognosis, as well as a promising target for treatments. This review aims to systematically summarize the gene polymorphism, expression profiles, biological roles, underlying mechanisms, and clinical applications of MIR31HG in human diseases.